Wawasan Al-Qur’an tentang Pendidikan dan Pengajaran - Hisan Mursalin (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2024)
The important aspect of human life is education. Through education, a person can develop their potential andunderstanding of the world around him can be developed through education. In Islam, education has a very important role. The Al-Quran as the holy book of Muslims provides guidance and guidance in living life, including in matters of education. Education in the vision of the Al-Quran aims to guide individuals to achieve spiritual, moral and intellectual perfection, as well as forming a just, harmonious and prosperous society. This research uses a literature review approach which focuses on data collection and comprehensive analysis of material or theories from various sources, including articles related to the topic discussed. The Al-Qur'an provides insight into education and teaching by emphasizing the importance of knowledge, morals and holistic self-development. This includes moral, scientific, social, and spiritual learning to form individuals who have noble character, are knowledgeable, and contribute positively to society. Thus, education in the insight of the Al-Quran is very important in the lives of Muslims. Through the Al-Quran, we can learn good life values ​​and apply them in everyday life. As Muslims, we should understand and practice the teachings of the Al-Quran in living this life. Hopefully, with education in the insight of the Al-Quran, we can become good individuals and be useful to society.